O potrzebie badań kultury bezpieczeństwa z perspektywy sytuacji kryzysowej - Magiera, Maciej (Przegląd Strategiczny, 2013)
There are some deciding factors which contribute to forming a demand of comprehensive risk minimalizing means to demand of seeking some potential daily threats in order to their identification and liquidation. These factors are for example: new philosophy of security sciences, desire for keeping the current level of consumption, a dynamization of reality, high awareness or easiness of access to information. It seems that the security culture may support public administration in compliance with social obligations. Moreover, the security culture influence on the crisis management effectiveness and it is conducive to knowledge systematization which is so import and because of the theory which is still modified and week strengthen. Taking into consideration three components of the security culture (resources, an organization and a mentality), it is possible to notice that the efficient counteracting crisis situations would have never happened without a radical intervention into our mentality. From that perspectives the security culture specifies a convention and defines some standards and customs regulating and interpreting security policy of a state. It makes the selection of demanding solutions in crisis management easy.